HUBUNGAN PENGETAHUAN DAN PERILAKU KESEHATAN GIGI DAN MULUT DENGAN STATUS KEBERSIHAN GIGI DAN MULUT (OHI-S) DAN ANGKA KEJADIAN KARIES (DMF-T) DI SDN 03 TANJUNG RAYA 2 PONTIANAK TIMUR TAHUN 2026 - Rusmali Rusmali; Rita Herlina; Mery Sartika (Devote: Jurnal Pengabdian Masyarakat Global, 2026)
Indonesian society. Based on the Basic Health Research (Riskesdas) data (2018), the prevalence of dental caries in Indonesia is still relatively high. This study aims to analyze the relationship between knowledge and oral health behavior with oral hygiene status (OHI-S) and the incidence of dental caries (DMF-T) in 87 respondents. The method used was Purposive Sampling, and the statistical test was Spearman Correlation. The results obtained were an average knowledge score of 7.68 in the moderate category, behavior score of 6.61 in the moderate category, oral hygiene status (OHI-S) average of 2.1 in the moderate category, and dental caries incidence (DMF-T) average of 3.9 in the moderate category. There is a gap of 1.07 points between knowledge and behavior, indicating that good knowledge has not been fully realized in actual actions. It is recommended to implement further interventions focusing on improving behavior through training on proper toothbrushing, routine reminder guidance, and strengthening the role of oral and dental health cadres.